1992
DOI: 10.1104/pp.98.2.480
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Malate and Amino Acid Metabolism to Cytoplasmic pH Regulation in Hypoxic Maize Root Tips Studied Using Nuclear Magnetic Resonance Spectroscopy

Abstract: ABSTRACT31P., 13C-, and "IN-nuclear magnetic resonance spectroscopy were used to determine the roles of malate, succinate, Ala, Asp, Glu, Gin, and y-aminobutyrate (GABA) in the energy metabolism and regulation of cytoplasmic pH in hypoxic maize (Zea mays L.) root tips. Nitogen status was manipulated by perfusing root tips with ammonium sulfate prior to hypoxia; this pretreatment led to enhanced synthesis of Ala early in hypoxia, and of GABA at later times. We show that: (a) the ability to regulate cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
102
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 26 publications
7
102
0
1
Order By: Relevance
“…In vivo 14N NMR experiments showed that the cells contained a substantial ammonium pool at the start of the labeling period and that the size of this pool varied throughout the 18-h time course (data not shown). Increases in GABA, ranging from 5-fold in 24 h in rice shoots (Reggiani et al, 1988) to 100-fold (with a 7-fold increase in Ala) in 4 h in radish leaves (Streeter and Thompson, 1972a) have been observed previously in a wide range of plants under hypoxia (Streeter and Thompson, 1972a;Tsushida and Murai, 1987;Reggiani et al, 1988;Menegus et al, 1989;Fan et al, 1992;Roberts et al, 1992). However, in these studies oxygen-free nitrogen was supplied to ensure complete anaerobiosis, whereas in the experiments reported here the oxygen supply was only mildly restricted.…”
Section: Effect Of Oxygen Supply On Ammonium Assindationmentioning
confidence: 99%
See 4 more Smart Citations
“…In vivo 14N NMR experiments showed that the cells contained a substantial ammonium pool at the start of the labeling period and that the size of this pool varied throughout the 18-h time course (data not shown). Increases in GABA, ranging from 5-fold in 24 h in rice shoots (Reggiani et al, 1988) to 100-fold (with a 7-fold increase in Ala) in 4 h in radish leaves (Streeter and Thompson, 1972a) have been observed previously in a wide range of plants under hypoxia (Streeter and Thompson, 1972a;Tsushida and Murai, 1987;Reggiani et al, 1988;Menegus et al, 1989;Fan et al, 1992;Roberts et al, 1992). However, in these studies oxygen-free nitrogen was supplied to ensure complete anaerobiosis, whereas in the experiments reported here the oxygen supply was only mildly restricted.…”
Section: Effect Of Oxygen Supply On Ammonium Assindationmentioning
confidence: 99%
“…However, in these studies oxygen-free nitrogen was supplied to ensure complete anaerobiosis, whereas in the experiments reported here the oxygen supply was only mildly restricted. Increases in Ala (Streeter and Thompson, 1972a;Roberts et al, 1992) and glutamate (Roberts et al, 1992) have also been observed following the onset of hypoxia, and in the cas12 of hypoxic maize root tips the accumulation of Ala, glutamate, and GABA was enhanced by pretreatment with ammonium (Roberts et al, 1992). The accumulation of these amino acids is consistent with p&, being regulated, at least in part, by changes in primary metabolism because the synthesis of Ala, arising from the decarboxylation of malate as a rlrsult of malic enzyme activation by cytoplasmic acidosis, the conversion of Gln to glutamate, and the decarboxylation of glutamate to GABA are all proton-consuming reactions.…”
Section: Effect Of Oxygen Supply On Ammonium Assindationmentioning
confidence: 99%
See 3 more Smart Citations